2018
DOI: 10.1111/jeb.13279
|View full text |Cite
|
Sign up to set email alerts
|

Parallel evolutionary forces influence the evolution of male and female songs in a tropical songbird

Abstract: Given the important role that animal vocalizations play in mate attraction and resource defence, acoustic signals are expected to play a significant role in speciation. Most studies, however, have focused on the acoustic traits of male animals living in the temperate zone. In contrast to temperate environments, in the tropics, it is commonplace for both sexes to produce complex acoustic signals. Therefore, tropical birds offer the opportunity to compare the sexes and provide a more comprehensive understanding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 123 publications
0
7
0
Order By: Relevance
“…Another potential explanation is that genetic diversity has driven population repertoire size. However, sites with low genetic diversity (Baillie, 2011) did not have correspondingly low syllable diversity, suggesting song culture is not tightly constrained by genetic diversity in bellbirds (see also Graham et al, 2018). We suspect that between-site differences in repertoire size are more likely driven by competition level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another potential explanation is that genetic diversity has driven population repertoire size. However, sites with low genetic diversity (Baillie, 2011) did not have correspondingly low syllable diversity, suggesting song culture is not tightly constrained by genetic diversity in bellbirds (see also Graham et al, 2018). We suspect that between-site differences in repertoire size are more likely driven by competition level.…”
Section: Discussionmentioning
confidence: 92%
“…Three later studies on rufous-and-white wrens (Graham et al, 2017a(Graham et al, , 2018(Graham et al, , 2021 showed that song cultures of males and females can be similar in complexity, and appear to evolve in similar directions via acoustic adaptation and cultural drift. However, males and females differ in the relationship between dispersal distance and song-sharing with parents (Graham et al, 2017a), the speed of cultural change, and the relationship between immigration rate and cultural diversity (Graham et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Price, 2019), we have few studies within species to guide our understanding of the processes driving these patterns. In contrast to the vast literature on within-species geographic divergence in male signals (McLean & Stuart-Fox, 2014;Podos & Warren, 2007;Slabbekoorn & Smith, 2002;Velásquez, 2014), there are few studies for females in the visual modality (McCoy et al, 1997;McLean & Stuart-Fox, 2014;Obara et al, 2008;Roulin, 2003;Tuomaala et al, 2012) and fewer still in the acoustic modality (Graham et al, 2017(Graham et al, , 2018Mennill & Rogers, 2006;Odom & Mennill, 2012). Yet, it is worth noting that three studies (in butterflies and birds) that considered intraspecific geographic variation in both sexes found greater signal divergence in females than males across populations (Graham et al, 2018;Mennill & Rogers, 2006;Tuomaala et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the vast literature on within-species geographic divergence in male signals (McLean & Stuart-Fox, 2014;Podos & Warren, 2007;Slabbekoorn & Smith, 2002;Velásquez, 2014), there are few studies for females in the visual modality (McCoy et al, 1997;McLean & Stuart-Fox, 2014;Obara et al, 2008;Roulin, 2003;Tuomaala et al, 2012) and fewer still in the acoustic modality (Graham et al, 2017(Graham et al, , 2018Mennill & Rogers, 2006;Odom & Mennill, 2012). Yet, it is worth noting that three studies (in butterflies and birds) that considered intraspecific geographic variation in both sexes found greater signal divergence in females than males across populations (Graham et al, 2018;Mennill & Rogers, 2006;Tuomaala et al, 2012). The implications of female signal evolution, male mate choice/recognition, and their impact on speciation have received little attention in the literature, with a few relevant studies focusing primarily on fish and insects (Chung et al, 2014;Edward & Chapman, 2011;Jiggins et al, 2004;Roberts & Mendelson, 2017.…”
Section: Discussionmentioning
confidence: 99%
“…Four later studies on rufous-and-white wrens (Graham et al, 2017a(Graham et al, , 2018a(Graham et al, ,b, 2021 showed that song cultures of males and females can be similar in complexity, and appear to evolve in similar directions via acoustic adaptation and cultural drift. However, males and females differ in the relationship between dispersal distance and song-sharing with parents (Graham et al, 2017a), the speed of cultural change, and the relationship between immigration rate and cultural diversity (Graham et al, 2021).…”
Section: Introductionmentioning
confidence: 99%